Visible to Near‐Infrared Photodiodes with Advanced Radiation Resistance. Issue 3 (19th January 2022) - Brus, Viktor V.; Solovan, Mykhailo M.; Schopp, Nora; Kaikanov, Marat; Mostovyi, Andriy I.
Abstract: A new type of sub‐micron metal‐intrinsic semiconductor‐metal visible to near‐infrared (400–1600 nm) photodiodes based on a unique combination of radiation‐resistant functional materials: sapphire, TiN, MoOx, CdTe, Hg3 In2 Te6, and graphite is proposed. The promising optoelectronic characteristics are calculated in the scope of a comprehensive semi‐analytical model, based on the complementary fusion of numerical Transfer Matrix optical simulation with analytical Hecht and dark generation current equations. The findings demonstrate proof‐of‐concept next‐generation high‐performance optoelectronic devices with advanced radiation resistance. Moreover, a simple device engineering modification has revealed a significant optimization potential for considered photodiodes. Abstract : The present contribution proposes a new type of sub‐micron metal‐intrinsic semiconductor‐metal visible to near‐infrared (400–1600 nm) photodiodes with promising steady‐state and transient optoelectronic characteristics and advanced radiation resistance.